El gasto público y su incidencia sobre la inflación en el Ecuador, período 2000-2017. - Rea Loja, Christian Fernando (2020)
This research project determines the relationship between public spending and inflation in Ecuador from 2000 to 2017. First, through ordinary least squares method, the variables are identified in order to see if they are significant to explain the model or not. In addition, an analysis of the evolution and behavior of the intervened variables are carried out with the use of statistical tables and graphs. Subsequently, the Autoregressive Vectors (VAR) model was estimated. As results, they showed the causality in the sense of Granger that the variables of public spending explain the behavior of inflation. Then in the impulseresponse analysis and decomposition of the variance, they establish that inflation is affected by public spending shocks since these fiscal policy variables affect the behavior of inflation.